A phase 2, multicentre, open‐label trial (ACE‐LY‐003) of acalabrutinib in patients with relapsed or refractory marginal zone lymphoma. (21st July 2022) - Strati, Paolo; Coleman, Morton; Champion, Rebecca; Ma, Shuo; Patti, Caterina; Levy, Moshe Y.; Lossos, Izidore S.; Geethakumari, Praveen Ramakrishnan; Lam, Selay; Calvo, Roser; Higgins, Kara; Budde, Lihua E.
Summary: Acalabrutinib, a Bruton tyrosine kinase inhibitor, demonstrated greater selectivity and improved safety versus ibrutinib in a head‐to‐head trial in relapsed/refractory (R/R) chronic lymphocytic leukaemia. In the R/R marginal zone lymphoma (MZL) cohort (phase 2) of a phase 1b/2 trial (NCT02180711), 43 patients with MZL and at least one prior therapy received acalabrutinib 100 mg twice daily until disease progression or unacceptable toxicity [median age 69 years (range 42–84); median one (1–4) prior systemic regimens]. Median follow‐up was 13.3 months (range 0.5–45.5). Among 40 patients evaluable for response, investigator‐assessed overall response rate was 53% [95% confidence interval (CI) 36%–69%] with five (13%) complete responses. Tumour reduction occurred in 40 (93%) of the treated patients. Median time to response was 2.9 months (median duration of response not estimable). Estimated median progression‐free survival (PFS) was 27.4 months (12‐month PFS rate, 67%). Five patients died (disease progression, n = 4; septic shock, n = 1). Seventeen patients (40%) had grade 3 or higher adverse events (AEs), most commonly neutropenia (14%), anaemia, dyspnoea (7% each), fatigue and thrombocytopenia (5% each). Hypertension occurred in 5%; atrial fibrillation/flutter and major haemorrhage were not reported. AEs led to treatment discontinuation in three (7%) patients. Acalabrutinib was active and well tolerated in patients with R/R MZL.